2021
DOI: 10.3390/e23010092
|View full text |Cite
|
Sign up to set email alerts
|

Signal Fluctuations and the Information Transmission Rates in Binary Communication Channels

Abstract: In the nervous system, information is conveyed by sequence of action potentials, called spikes-trains. As MacKay and McCulloch suggested, spike-trains can be represented as bits sequences coming from Information Sources (IS). Previously, we studied relations between spikes’ Information Transmission Rates (ITR) and their correlations, and frequencies. Now, I concentrate on the problem of how spikes fluctuations affect ITR. The IS are typically modeled as stationary stochastic processes, which I consider here as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Knoblauch et al [59] examined the relationship between noise and inter-spike-interval statistics in real neurons in working brains. Pregowska [60] explored how spike fluctuations affect the information transmission rates. Moreover, how neurons communicate is also an important aspect of studying brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Knoblauch et al [59] examined the relationship between noise and inter-spike-interval statistics in real neurons in working brains. Pregowska [60] explored how spike fluctuations affect the information transmission rates. Moreover, how neurons communicate is also an important aspect of studying brain function.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that improved transmission properties in the case of limited visibility were obtained for a wavelength of about 10 µ m, compared to the near-infrared waves. Analogous situations related to the selection/determination of appropriate parameters of the sources generating signals being sent through noisy transmission channels to improve the transmission efficiency also occur in classic transmission channels [28][29][30][31][32][33].…”
Section: Methodsmentioning
confidence: 99%
“…Since the literature of neuroscience is vast [39], we will not review it here, but we do want to highlight some progress in neuroscience that can potentially inspire and improve current machine learning systems. The study of neural codes [40], neural information processing and transmission [41][42][43], and neural spikes [44] may provide tools and language towards the study and design of artificial neural networks.…”
Section: Related Workmentioning
confidence: 99%